A Hybrid Uniplanar Pedicle Screw System with a New Intermediate Screw for Minimally Invasive Spinal Fixation: A Finite Element Analysis. (19th November 2020) - Li, Jia; Zhang, Li-Cheng; Li, Jiantao; Zhang, Hao; Zhao, Jing-Xin; Zhang, Wei
Abstract : Purpose. A hybrid pedicle screw system for minimally invasive spinal fixation was developed based on the uniplanar pedicle screw construct and a new intermediate screw. Its biomechanical performance was evaluated using finite element (FE) analysis. Methods. A T12-L2 FE model was established to simulate the L1 vertebral compression fracture with Magerl classification A1.2. Six fixation models were developed to simulate the posterior pedicle screw fracture fixation, which were divided into two subgroups with different construct configurations: (1) six-monoaxial/uniplanar/polyaxial pedicle screw constructs and (2) four-monoaxial/uniplanar/polyaxial pedicle screw constructs with the new intermediate screw. After model validation, flexion, extension, lateral bending, and axial rotation with 7.5 Nm moments and preloading of 500 N vertical compression were applied to the FE models to compare the biomechanical performances of the six fixation models with maximum von Mises stress, range of motion, and maximum displacement of the vertebra. Results. Under four loading scenarios, the maximum von Mises stresses were found to be at the roots of the upper or lower pedicle screws. In the cases of flexion, lateral bending, and axial rotation, the maximum von Mises stress of the uniplanar screw construct lay in between the monoaxial and polyaxial screw constructs in each subgroup. Considering lateral bending, the uniplanar screw construct enabled to lower the maximum von Mises stress than monoaxial and polyaxial pedicle screw constructs in each subgroup. Two subgroups showed comparable results of the maximum von Mises stress on the endplates, range of motion of T12-L1, and maximum displacement of T12 between the corresponding constructs with the new intermediate screw or not. Conclusions. The observations shown in this study verified that the hybrid uniplanar pedicle screw system exhibited comparable biomechanical performance as compared with other posterior short-segment constructs. The potential advantage of this new fixation system may provide researchers and clinical practitioners an alternative for minimally invasive spinal fixation with vertebral augmentation.